Active RFID Technology for Asset Tracking and Management System - Evizal Evizal; Tharek Abdul Rahman; Sharul Kamal Abdul Rahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Asset is one of valuable item in the industry or institution, missing or lose of asset may have problem in asset management system. The advantages of Radio Frequency Identification (RFID) technology have made this technology useful for asset management and tracking system. The use of active RFID technology for asset tracking is by attaching the tag at the asset or item with assigned a unique ID for identification. A few of active RFID readers install at strategic points or location to track asset movement and collect information when anyone of item pass by in reader coverage area, reader collect information with in reading range and send to backend system. Integration every single system by using wires or wireless methods to keep centralize data processing system. Alert message will be send to representative department to give warning. This asset tracking and management system that use active type of RFID technology is working at ISM band frequency of 433 MHz. The backend systems consist of application software, middleware and database. All the information have been sent from every single system recorded in one central database.